Efficacy of Resuscitative Infusion With Hemoglobin Vesicles in Rabbits With Massive Obstetric Hemorrhage. Issue 1 (March 2022) - Yuki, Y.; Hagisawa, K.; Kinoshita, M.; Ishibashi, H.; Kaneko, K.; Ishida, O.; Saitoh, D.; Sakai, H.; Terui, K.
Abstract : ( Am J Obstet Gynecol . 2021;224:398.e1–398.e11. doi: 10.1016/j.ajog.2020.09.010. Epub September 12, 2020) Massive transfusion protocol (MTP) is a management strategy for massive obstetric hemorrhage (MOH), an unpredictable birth complication, yet small maternity clinics and birth centers don't always have access to MTP. Red blood cell (RBC) transfusion is optimally administered to patients requiring resuscitative infusion following MOH, but there are logistical limitations to providing small maternity clinics and birth centers with the supplies required for treatment. Thus, hemoglobin vesicles (HbVs) have been developed and tested as an RBC transfusion substitute with a much more practical and stable shelf life, making it much more affordable for small hospitals to have on hand. Though HbVs are logistically beneficial, there are questions around its efficacy and safety, so animal models have been developed to address these. This study used a rabbit model to substitute RBC transfusion with MOH to show efficacy of HbVs in rabbits with MOH.